Analisis Konflik Tokoh Utama Novel Hakuchō to Kōmori karya Keigo Higashino - Masyrifah, Nurul; Anwar, Fithyani (NAWA: Journal of Japanese Studies, 2025)
Character conflicts are divided into two, namely external and internal conflicts. This study aims to describe the conflict of the main character, Tatsuro Kuraki, and analyze the cause of the conflict in the novel Hakuchō to Kōmori by Keigo Higashino. This research uses a structural approach with a descriptive qualitative method. The analysis shows that one of the main characters' external conflicts is between Tatsuro Kuraki and Shozo Haitani. Tatsuro accidentally grazed Haitani, so Haitani threatened to report Tatsuro. Furthermore, internal conflict is in the form of Tatsuro's guilt towards the Asaba family, who were victims of police misapprehension in the case of Haitani's death. Furthermore, one of the factors causing conflict in Tatsuro's character is Tatsuro's pity for Shiraishi, who is still a teenager, so he covers up the murder of Haitani committed by Shiraishi. The overall conflict that occurs in the main character has a significant influence on the formation of the plot and other elements in the story.